Electric Vehicle Regulation: Navigating Legal Challenges in Sustainable Transportation Transformation - Meutia Nadia Karunia; Muhammad Abi Berkah Nadi; Rudy Max Damara Gugat; Resma Bintani Gustaliza (PT. Anagata Sembagi Education, 2025)
The global adoption of electric vehicles (EVs) continues to increase in line with efforts to reduce carbon emissions and achieve sustainable transportation. The Indonesian government targets 2 million electric cars and 13 million two-wheeled electric vehicles by 2030, with various fiscal incentives and subsidies. However, EV adoption still faces major challenges, including high prices compared to conventional vehicles, limited charging infrastructure, and regulations that have not been fully integrated. The complexity of regulations, including the 38 Indonesian National Standards (SNI) that are still voluntary, hinders the acceleration of the EV industry. In addition, regulations related to battery waste management and carbon footprint in electric vehicle production still need to be strengthened. This study uses normative juridical methods with legislative, conceptual, and comparative legal approaches to analyze the effectiveness of EV regulations in Indonesia compared to other countries. The results of the study show the need for regulatory harmonization, the application of the Extended Producer Responsibility (EPR) principle for battery recycling, and the integration of environmental policies in EV development. With more structured policies and collaboration between the government, industry, and society, Indonesia can accelerate the adoption of electric vehicles effectively and sustainably, while reducing environmental impact and increasing the competitiveness of the national industry